(untitled) (Eurasian Journal of Engineering and Technology, 2024)
The Aral Sea region of Uzbekistan — Karakalpakstan and Khorezm — experiences combined air, water and soil pollution from the desiccated seabed, saline drainage waters and legacy organochlorine pesticides. The cumulative impact on population health remains poorly quantified at sub-regional resolution. Objective. To examine, across 25 administrative districts, the association between a composite pollution index (CPI) and five ecology-sensitive disease groups: respiratory, cardiovascular, oncological, endocrine, and infant/maternal. Methods. An ecological cross-sectional design with longitudinal supplements was used. Age-standardised disease rates (2010–2023) were extracted from official registers. CPI was the unweighted mean of normalised US EPA AQI, CCME WQI and Håkanson–Müller soil indices. Spearman rank correlation and multivariable linear regression with sociodemographic adjustment were applied. Results. Disease rates were highest in Moynak — asthma 814, COPD 590, hypertension 2,840, IHD mortality 264, cancer 268 per 100,000 and infant mortality 24.8 per 1,000. CPI correlated with all five outcomes (r_s 0.70–0.82). Adjusted models confirmed the associations. Conclusions. Composite pollution is strongly and consistently associated with ecology-sensitive disease burden; multi-media mitigation in northern Karakalpakstan is urgent.